Development of an oral vaccine against Clostridioides difficile - Karyal, Cansu (2021)
Clostridioides difficile (C. difficile) is the leading cause of hospital acquired diarrhoeal infection. The major risk factors associated with C. difficile infection (CDI) is age (65 and over), use of broad-spectrum antibiotics and prolonged hospital stays. Symptoms range from mild diarrhoea to life threatening fulminant colitis. Clinical manifestation is mainly due to two toxins; TcdA and TcdB. The failure to treat recurrent infection can culminate in death and thus preventative measures are of urgent need. Current vaccine trials in humans are exclusively focused on parenteral delivery of toxin-based formulations. These vaccines elicit toxin-neutralising serum antibody responses, however they fail to provide protection against CDI which occurs in the gut. A more effective way to vaccinate against this gut pathogen would be with a mucosal vaccine via the oral route. This would potentially generate a local mucosal immune response, i.e., secretory IgA (sIgA) that directly targets the site of infection. Mucosal vaccines require adjuvants to elicit potent immune responses. Bacterial lipoproteins harbour intrinsic adjuvant properties due to their lipid moiety interactions with Toll-like receptor 2 (TLR2) found on antigen presenting cells (APCs) which leads to APC activation and antigen uptake. Thus, synthetic bacterial lipids that act as TLR2 agonists have been extensively studied through their attachment to synthesised peptides to serve as potential adjuvants. However, using synthetic peptides allow for recognition of only smaller immunogenic fragments/epitopes which limits their target for whole proteins. We set out to formulate an oral mucosal vaccine using recombinant C. difficile antigens expressed with a unique N-terminal cysteine used to conjugate a synthetic lipid with a maleimide head group, to mimic bacterial lipoproteins. These semi-synthetic lipoproteins were presented on liposomes as a delivery vehicle and to also mimic the native presentation of lipoproteins on the bacterial cell surface. In this study we tested two antigens; colonisation factor CD630_08730 and a fragment of the receptor binding domain of TcdB and compared these administered either as antigen alone or with being presented on liposomes with conjugation to a lipid adjuvant. The formulations were lyophilised and packed into enteric coated capsule. Hamsters immunised with both CD630_08730 formulations showed strong intestinal sIgA and serum IgG responses compared to the naïve group and other control groups, which reduced C. difficile adherence to Caco-2 cells in vitro. The adherence blocking was further reduced for those hamsters receiving CD630_08730 adjuvanted with the synthetic lipid, presented on liposomes compared to the antigen alone. As hamsters receiving CD630_08730 alone showed good immunological responses, its protective efficacy was tested. Hamsters immunised with CD630_08730 antigen alone were challenged with hypervirulent strain R20291ermB and showed an 80% increase in mean time to end point compared to naïve animals. The survival was correlated with bacterial clearance and reduced toxin-mediated damage as determined from histopathology assessment of the caecum. This study highlights the potential of using semi-synthetic lipoproteins presented on liposomes as an oral vaccine platform and also highlights the potential of CD630_08730 as a vaccine candidate against CDI.